Faktor-Faktor Pendukung Keberhasilan Perusahaan Media Massa di Era Digital dalam Perspektif Studi Literatur - Nessy; Mega Wahyu Lestari; Ade Rosad; Leni Suciati (Penerbit Jurnal Indonesia, 2026)
The development of information and communication technology in the digital era has driven major changes in the mass media industry, particularly in the patterns of production, distribution, and consumption of information. This study aims to identify and analyze the factors supporting the success of mass media companies in the digital era through a literature study approach. The research method used is descriptive qualitative with a library research approach. Data were obtained from various national and international scientific journals, academic books, and scientific publications relevant to digital media transformation. The data analysis technique used content analysis through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the success of digital mass media companies is influenced by five main factors, namely: (1) integrated digital business model transformation; (2) the use of artificial intelligence (AI) in increasing the efficiency of content production and distribution; (3) multiplatform distribution strategies based on SEO and audience interactivity; (4) human resource competencies that are multitasking and adaptive to technology; and (5) an innovative organizational culture supported by transformational leadership. This study also found that the implementation of digital technology will not run optimally without human resource readiness and a flexible organizational culture. Therefore, the success of mass media in the digital era is determined not only by technological sophistication, but also by the organization's ability to integrate innovation, change management, and journalistic professionalism sustainably. The findings of this study are expected to serve as theoretical and practical references for developing media company strategies amidst digital disruption.